Analysis Of Dhikr Toward Peace Of Mind: Islam In Psychological Approach - Helma Winda (ASTEEC, 2023)
Increasingly Modern Era Of Human Life, There Are Various Kinds Of Problems In Life, Dissatisfaction With Life, And Insatiable Desires. This Makes Humans Neglect Their Faith And Distance Themselves From Allah, The Creator. The Dissatisfaction Experienced By Humans Causes Various Kinds Of Psychological Turmoil That Can Have A Negative Impact On The Life Process. The Method Used In Writing This Article Is The Theoretical Study Method, Retrieving Information Through The Process Of Reading, Recording, Collecting Information From Various Sources Such As Books, Journals, And Several Other References Which Are Then Used As References And Reviewing Theoretical Studies. In Islam, The Turmoil Experienced By Humans That Causes Anxiety, Discomfort, And Unease Can Be Handled With Efforts That Have Been Contained In The Qur'an Based On The Words Of Allah And Hadith, Namely By Means Of Dhikr. Through Dhikr, Humans Can Remember Allah, So That It Will Not Focus Too Much On Worldly Life Which Has No Limit To Achieving Satisfaction. Dhikr Can Be Used As A Therapy For The Human Psyche. So That Through This Dhikr Can Create Humans Who Have Faith And Are Close To Allah. Through This Dhikr, Peace Of Mind Can Be Created So That Humans Can Increase Their Faith And Return To Allah's Guidance.